Uganda : Seventh Review Under the Policy Support Instrument-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
The economy has performed reasonably well in a complex environment. Growth slowed marginally in FY15/16, reflecting muted sentiment in an election year and adverse global and regional developments. Growth should nudge up in FY16/17 to 5 percent, low compared to past performance and regional peers. Credit to the private sector has stalled, and non-performing loans (NPLs) have increased, also reflecting domestic government arrears. The current account deficit is fully financed. The Shilling has stabilized after a sharp depreciation in 2015, and international reserve coverage remains adequate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet